2007
DOI: 10.1017/s002966510700568x
|View full text |Cite
|
Sign up to set email alerts
|

Session 4: Mineral metabolism and body composition Iron status of breast-fed infants

Abstract: Fe deficiency is a common nutritional disorder during infancy, particularly in low-income countries. The Fe status of a breast-fed infant is strongly influenced by the body Fe content at birth, which is determined by factors that operate before birth (maternal Fe status before and during pregnancy; infant gestational age and birth weight) and at the time of delivery (the timing of umbilical cord clamping). Delaying the clamping of the umbilical cord for 2 min can increase body Fe content by approximately 33% (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
90
0
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(99 citation statements)
references
References 52 publications
2
90
0
7
Order By: Relevance
“…[1][2]5 In utero, at term gestation, one-third of the fetus's blood volume is in the placenta at any one time. At the time of birth, a major shift occurs in the cardiac output to the lungsFchanging from 8 to 10% in fetal life to 50% in neonatal life.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[1][2]5 In utero, at term gestation, one-third of the fetus's blood volume is in the placenta at any one time. At the time of birth, a major shift occurs in the cardiac output to the lungsFchanging from 8 to 10% in fetal life to 50% in neonatal life.…”
Section: Discussionmentioning
confidence: 99%
“…1 When the cord is cut immediately, the infant does not receive the additional blood volume from placental transfusion, representing a loss of 25 mg kg -1 of iron or 33% less body iron. 2 This loss can affect iron stores and may place the infant at risk for iron deficiency and anemia during infancy. [1][2][3][4][5] Although delaying the clamping and cutting of the cord at birth optimizes placental transfusion, it is not always feasible at the time of cesarean section.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have shown that supplementation during pregnancy may not be necessary (13) and may increase the risk of LBW and on the contrary others suggest that supplementation is recommended (14) . Furthermore some workers suggest that breastfeeding is protective for infants (15,16) and for the breastfeeding mother by preserving and building her iron stores. This is achieved by enhancing absorption of iron and preventing blood loss and inducing lactational amenorrhea (17) .…”
Section: Introductionmentioning
confidence: 99%